Glocalisation, English and Singlish: Creating a Singaporean Identity - Prakash, Pravin (2016)
The English versus Singlish debate reflects an element of the social fabric of Singapore. The concept of glocalisation brings a deeper understanding to a weak argument on Singlish’s role and imperative for competence in English. The need to redouble efforts at teaching Standard English is underlined.